Serial Magnetic Resonance Imaging (MRI) in Pyruvate Dehydrogenase Complex Deficiency. (February 2020) - Shelkowitz, Emily; Ficicioglu, Can; Stence, Nicholas; Van Hove, Johan; Larson, Austin
Objectives: To report 2 additional cases of pyruvate dehydrogenase complex deficiency with reversible deep gray matter lesions following initiation of ketogenic diet and to perform a literature review of serial imaging in patients with pyruvate dehydrogenase complex. Methods: Clinical data on 3 previously unpublished cases of patients with pyruvate dehydrogenase complex deficiency and with serial magnetic resonance imagings (MRIs) before and after institution of ketogenic diet were reported. A systematic literature review was performed to search for published cases of patients with confirmed pyruvate dehydrogenase complex deficiency who underwent serial MRIs. Results: The 3 subjects in this series demonstrated clinical improvement on ketogenic diet. Two subjects showed reversal of some brain lesions on repeat MRI following initiation of ketogenic diet. Of the 21 published cases with serial MRIs, 13 patients underwent some form of treatment, and of this smaller subset 4 patients had repeat MRIs that showed definitive improvement. In both our described cases and those published in the literature, improvement occurred in lesions in the basal ganglia. Conclusions: In patients with pyruvate dehydrogenase complex deficiency, basal ganglia lesions on MRI are reversible with treatment in some cases and could serve as a biomarker for measuring response to treatment.